2010
DOI: 10.1590/s0104-42302010000400025
|View full text |Cite
|
Sign up to set email alerts
|

O papel das selenoproteínas no câncer

Abstract: Evidence has shown that metabolic disorders are common in tumor cells, leading to increased oxidative stress. The increase in the production of reactive oxygen species (ROS) associated with low antioxidant activity has been related to several types of cancer. Selenium, an antioxidant micronutrient, may function as an antimutagenic agent, preventing the malignant transformation of normal cells. A review of the literature was conducted based on a survey of articles published between 2000 and 2009 in the PubMed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 61 publications
0
7
0
4
Order By: Relevance
“…In addition, it can act in the formation of hormones, in DNA synthesis, fertility, reproduction, increasing muscle functions, and delaying the aging process (Suttle, 2010;Cabaraux et al, 2006). Furthermore, there are reports of cancer prevention through the action of selenoenzymes, which reduce damages caused to the DNA and decreases reactive oxygen species, increasing the production of tumor suppressor proteins (Almondes et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it can act in the formation of hormones, in DNA synthesis, fertility, reproduction, increasing muscle functions, and delaying the aging process (Suttle, 2010;Cabaraux et al, 2006). Furthermore, there are reports of cancer prevention through the action of selenoenzymes, which reduce damages caused to the DNA and decreases reactive oxygen species, increasing the production of tumor suppressor proteins (Almondes et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A selenometilselenocisteína é o principal composto de selênio encontrado em vegetais como alho, cebola, brócolis e alho poró. 13 A presença ou combinação de alguns fatores como concentração de proteínas, vitaminas E e A na dieta, presença de inibidores como metais pesados (cádmio, mercúrio e enxofre), a própria concentração de selênio, bem como a forma química do mineral presente na dieta podem influenciar a sua biodisponibilidade. Outros fatores, como as interações ocasionadas pela ingestão de compostos presentes na dieta, tais como o conteúdo de fitatos, pectina e fibras totais podem reduzir a biodisponibilidade do selênio.…”
Section: Aspectos Metabólicos E Fisiológicos Do Selêniounclassified
“…The protective effect of this mineral is especially associated with its presence in glutathione peroxidase and thioredoxin reductase, enzymes that protect the DNA and other cellular components against oxidative damage caused by ROS. Several studies have demonstrated reduced expression of these enzymes in various types of cancer, especially when associated with a low intake of selenium, which may exacerbate the damage (Almondes et al, 2010). A total of 1312 patients (mean age, 63 years; range, 18-80 years) with a history of basal cell or squamous cell carcinomas of the skin were randomized from 1983 through 1991.…”
Section: Seleniummentioning
confidence: 99%